A Survey on Mobile based ERP system (M-ERP) - Kulshrestha, Akshay; Patel, Jinal; Deshmukh, Pornima; Krishnani, Lavina (International Journal of Computer Sciences and Engineering, 2025)
Since ages, marking attendance and other similar college functions has been most important activities of any school, college to keep records. This record helps the organization in generating their month-end progress report etc such system may be manual or automated. In proposed system, an attempt has been made to develop and deploy M-ERP application on Android mobile phones. The advancement in the mobile devices, wireless and web technologies gives rise to new application that makes ERP system very easy and convenient. M-ERP means performing college register functions by using portable mobile device. M-ERP application will integrate all the business functions like marking attendance, marks, Student information etc in a single centralized database. M-ERP promising the possibility of convenient, easy and safe way to handle business functions of college. We have described how the android mobile phones are efficient and can be used for ERP system.